Perilaku Seismik Struktur Rangka Komposit RCS dengan Variasi Rigidity Zone Factor Pertemuan Balok-Kolom - Sudarsana, I Ketut; Susila, I Gede Adi; Sastraningsih, Ni Wayan (Department of Civil Engineering, Diponegoro University, 2021)
This research evaluated the effect of connection’s rigidity zone factors of RCS frame’s connections on the seismic behavior of regular RCS frames of a five-story office building located at seismic design category (SDC) of D. The variations on rigidity zone factors were 0, 0.25, 0.50, 0.75, and 1.0, respectively for Model MS, MSR025, MSR05 MSR075, and MR with the same elements’ dimension. A 3-D finite element modeling was conducted to do a linear elastic analysis for structural design and nonlinear static pushover analysis for evaluating the structural seismic performance. The results show that all models have met the strength and serviceability design limits. The seismic performances in terms of base shear, elastic stiffness, and ductility of all RCS models increased with an increase in the values of the rigidity zone factor. The structural performance level according to FEMA 440 was life safety (LS) for the Model MSR05, MSR075, and MR, while for the Model MS and MSR025 was collapse prevention (CP). The seismic energy dissipation for all RCS frames was an intermediate category indicated by the numbers of developed plastic hinges less than 20% of the total potential plastic hinges